1035-P: Early Pregnancy Alterations in the Metabolome of Obese Women - BANDRES-MERIZ, JULIA; KUNZ, CHRISTINA; HAVELUND, JESPER; FÆRGEMAN, NILS J.; HURTADO DE MENDOZA, IRENE; MAJALI-MARTINEZ, ALEJANDRO; ENSENAUER, REGINA; DESOYE, GERNOT (Diabetes (New York, N.Y.), 2022)
Obesity in human pregnancy associates with changes in the glucose-insulin axis. We hypothesized that these changes affect the maternal metabolome already in the first trimester, and thus aimed to identify these metabolites. We performed untargeted metabolomics (HPLC-MS/MS) on maternal serum (n=111, gestational age week 4+0-11+6) . In addition to BMI and leptin as measures of obesity and adiposity, we metabolically phenotyped women by their fasting glucose, C-peptide and insulin sensitivity index (ISHOMA) . We identified 2449 serum metabolites of which 277 were annotated. After stringent filtering employing a combination of univariate and multivariate analyses with multiple confounders and machine learning methods (Partial Least Squares Discriminant Analysis, Random Forest and Support Vector Machine) we identified 14 metabolites robustly and significantly (FDR<0.1) associated with at least one exposure (BMI, leptin, glucose, C-peptide, ISHOMA) . Among these, palmitoleoyl ethanolamine (POEA) , an endocannabinoid-like lipid endogenously synthesized from palmitoleic acid, was consistently associated with C-peptide in all analyses explaining 21% of variance in POEA concentration. Decreased POEA levels in T2D and its affinity for the novel endocannabinoid GRP1receptor made it a strong candidate for further exploration. In network analysis most metabolites correlating with POEA and regulated by C-peptide, were amino acids or dipeptides (n=9, 35%) , followed by lipids (n=7, 27%) . We conclude that the metabolome of overweight/obese pregnant women is already altered early in pregnancy. Changes of POEA concentration in pregnant women with obesity-associated hyperinsulinemia may reflect dysfunctional endocannabinoid signalling and, thus, compromise pregnancy maintenance.